UiTM Green Centre conducted a visit to the lifeline clothing Malaysia factory in Port Klang, Selangor - UiTM, UGC (UiTM Green Centre, 2025)
On 13 March 2025, UiTM Green Centre conducted a visit to the lifeline clothing Malaysia factory in Port Klang, Selangor, to observe clothing recycling techniques and processes implemented at the facility.